Characterization of a new Carlavirus isolated from football lily (Scandoxus katharine) in India - R. P. PANT* and Y. S. AHLAWAT, D. R. DAS, LOKENDRA SINGH (Indian Phytopathology, 2010)
In India, football lily (Scandoxus katharine) is commonly grown in nurseries as ornamental flower. It is naturally occuring plant in Sikkim and Darjeeling hills. Virus-like symptoms were observed in various nurseries at Delhi, Meerut, Sikkim and Kalimpong. Electron microscopic observation revealed flexuous particles measuring 650 x 13nm constantly associated with the disease. Samples from naturally affected plants were collected and maintained in glass house. The disease was mechanically transmitted to football lily and Chenopodium amaranticolor only. A filamentous virus was partially purified from glasshouse inoculated football lily plants. Polyclonal antibodies against the virus were developed and used for virus detection in ELISA. Virus associated with football lily mosaic disease had single coat protein of 31kDa. It was serologically related to carnation latent virus. Ultra thin sections of infected tissue revealed large number of virus particles scattered in the cytoplasm but not in nucleus. No inclusion bodies characteristic of potyvirus was observed. Particle morphology, transmission, serological relationship, size of coat protein and absence of characteristic inclusion bodies suggests that the virus may be a member of Carlavirus group. Tentatively, the virus associated with football lily mosaic disease has been named as ‘Football lily mosaic carlavirus’ (FLMCV).